A NOTE ON AN R- MODULE WITH APPROXIMATELY-PURE INTERSECTION PROPERTY - Al-Hassani, Uhood S (Al-Nahrain Journal of Science, 2010)
Let R be a commutative ring with identity and Let M be left R module. A submodule Nof an R- module M is said to be approximately-pure submodule of M (for short AP-pure), ifNIM  IN+J(R)M(NIM), for each ideal of R. the main purpose of this paper is to develop theproperties of modules with the approximately- pure intersection property M